The effectiveness and safety of electroacupuncture for nonspecific chronic low back pain: A protocol for systematic review and/or meta-analysis. Issue 4 (29th January 2021) - Sung, Won-Suk; Park, Jeong Ryul; Park, Kyungbok; Youn, Inae; Yeum, Hye Won; Kim, Sungyoon; Choi, Jieun; Cho, Yeeun; Hong, Yejin; Park, Yeoncheol; Kim, Eun-Jung; Nam, Dongwoo
Abstract: Background: Low back pain (LBP) is a common symptom that affects almost 80% of the global population. LBP manifests as diverse pathologies and has different causes. The focus of this paper is nonspecific chronic low back pain (NSCLBP) wherein the pain lasts for more than 12 weeks, and for which there is no definite cause. Although there are various treatment options for NSCLBP, including medication and exercise, each option has its own limitations. Although electroacupuncture (EA) has been known to have useful analgesic effects on chronic LBP, there is no systematic review (SR) on EA in the literature. Therefore, this study aims to systematically review and validate the effectiveness and safety of EA for NSCLBP. Methods: We will search for randomized controlled trials on the use of EA for NSCLBP in multiple electronic databases, manual searches, and contacting authors. We will screen and select studies according to the predefined criteria and extract the data needed for this SR. The primary outcome will be the pain index (Visual Analog Scale and Numeric Rating Scale), and the secondary outcomes will be the functional status (Roland-Morris Disability Questionnaire), patient-centered outcomes, and adverse events. We will perform a meta-analysis using Review Manager software (Version 5.3; Copenhagen; The Nordic Cochrane Center, The Cochrane Collaboration, 2014) and assess the risk of bias using Cochrane Collaboration "risk of bias" tools and the quality of evidence using the Grades of Recommendation, Assessment, Development and Evaluation. Results: Our SR will investigate the effectiveness and safety of EA on NSCLBP. Conclusion: Our SR will support the published clinical evidence of the usage of EA for NSCLBP to assess the effectiveness and safety of EA. Trial registration number: INPLASY; INPLASY2020120039